Pengaruh Penggunaan Smartphone Terhadap Prestasi Belajar Siswa Kelas Vi Sd Negeri 06 Kendari - Sahlun Sahlun; Ashari Usman; Ahmad Ahmad (Prodi PGSD Unsultra, 2021)
This study aims to determine the extent of the effect of smartphone use on students’ learning achievement, particularly among sixth-grade students at Elementary School 6 Kendari. This research employed a quantitative approach. The population consisted of all sixth-grade students totaling 245, and a systematic random sampling technique was used to select 50% or 61 students as the research sample. Data were collected through questionnaires, direct observation, and documentation of student report scores. The data were analyzed using a simple linear regression statistical formula. The results showed that the correlation value (R) was 0.437, and the coefficient of determination (R²) was 0.191, indicating that the independent variable influenced the dependent variable by 19.1%, while the remaining 80.9% was influenced by other factors. The t-test results revealed that the calculated t-value was 3.733 with a significance value of 0.000 < 0.05, meaning that H₀ was rejected and Hₐ accepted. Therefore, there is a significant effect of smartphone use on student learning achievement. It can be concluded that when smartphone use decreases by one unit, student learning achievement increases by 0.158.